Social Modality for Post Flood Disaster Cimanuk River in Garut Regency - Indra Kristian; Bambang Heru Purwanto; Yaya Mulyana Abdul Azis (Pasundan Social Science Development, 2021)
Based on the observation that the implementation of Disaster Management in Garut Regency has not been implemented optimally. This is evident from the fact that there are still many victims when a disaster occurs so that overall handling is still necessary. The research method used is qualitative. The type of qualitative approach used is descriptive. Qualitative research is a research procedure that produces descriptive data in written or spoken words from people and observable behavior. The qualitative method was chosen considering that this method is expected to obtain accurate data and examine research problems in depth so that the expected results can be obtained. The term gotong royong cannot be underestimated in a foreign language because gotong royong is the familiar spirit of the Indonesian people to unite, cooperate, share, help each other, and feel together to achieve common goals with benefits for all. The term gotog royong is often heard, but this social spirit is starting to weaken, especially in cities. Restoring the spirit of gotong royong today is quite a challenge today. However, participation and participation in a community group are the key to life's values to carry out a strategy in life.